Numerical study on the behavior of blasting in deep rock masses - Li, Xiaohan; Zhu, Zheming; Wang, Meng; Wan, Duanying; Zhou, Lei; Liu, Ruifeng (Tunnelling and underground space technology, 2021)
•The RHT model was used to simulate the rock material and was calibrated.•The stress initialization was achieved in the first step of the simulation.•In-situ stresses can increase the compressive stress and reduce the tensile stress.•Both the crushed zone and the cracked zone are inhibited by in-situ stresses. High in-situ stress can limit the generation of rock fractures induced by blasting, which usually shows different states of rock fragmentation with those under low-stress conditions. In this paper, the stress distribution around the blasthole under coupled in-situ stress and blasting load was theoretically analyzed. Then, the single-blasthole blasting process, which is calibrated by field blasting tests, was numerically investigated using the Riedel-Hiermaier-Thoma (RHT) model, and the effects of in-situ stress magnitudes and lateral pressure coefficients on the crushed zone and the crack propagation were investigated. After that, influences of lateral pressure coefficients, buried depths, and blasthole layouts on the behavior of double-blasthole blasting were studied. It is concluded that in-situ stresses can increase the compressive stress and reduce the tensile stress caused by blasting load. The area of the crushed zone decreases with increasing in-situ stresses. The crushed zone is elliptical in shape in anisotropic pressure conditions. The gap between the long axis and the short axis of the crushed zone widens as the difference between the stress in the horizontal and vertical directions increases. Cracks preferentially propagate in the higher stress direction. At a buried depth of 1000 m, connecting cracks can be formed at lateral pressure coefficients ranging from 0.25 to 3.0 when blastholes are drilled along the horizontal direction. The rise in buried depths and the angle between the centerline of adjacent blastholes and the higher stress direction can limit the formation of connecting cracks. The research results can provide guidance for analyzing the behavior of rock blasting in deep underground.